Parental knowledge, attitude and practice on malaria in Mandailing Natal district - Syafruddin Haris; Sri Sofyani; Bidasari Lubis; Munar Lubis; Syahril Pasaribu; Iskandar Z. Lubis (Indonesian Pediatric Society, 2007)
Background Malaria is still considered to be an important healthproblem in Indonesia. Malaria has been found in islands withdifferent degree of endemicity. Behavior of the community isone of the factors affecting the incidence of malaria in MandailingNatal district.Objective To know the parental knowledge, attitude, and practiceamong parents whose children suffered from malaria or not.Methods A cross sectional study was conducted in six primaryschools and one health centre in October 2004. Subjects wereparents whose children were malaria positive and malaria negativebased on laboratory examination. Sample size was 85 parents foreach group. Selected respondents were interviewed usingstructured questionnaire. Degree of knowledge, attitude, andpractice on malaria were established using scoring system withinthree categories: good, less, and poor. Data were collected andpresented using chi-square and P<0.05 was considered as a levelof significant.Results The mean age of 85 parents whose children were positivemalaria, was 38.47 years (SD 6.67) and the mean age of thosewhose children were negative malaria was 40.41 years (SD 8.05).Parent’s education level was 62.9% primary school and 90% oftheir children were school-aged. There were significant differenceson parental knowledge, attitude and practice in each group(P<0.05). There was also a significant correlation betweenoccupation and knowledge, but not between parental educationlevel and parental age. Parental knowledge and attitude on theincidence of malaria in Mandailing Natal district were good,though their practice were poor.Conclusion There are significant differences on parentalknowledge, attitude and practice, between parents whose childrenwere positive and negative for malaria.